Suberosin attenuates rheumatoid arthritis by repolarizing macrophages and inhibiting synovitis via the JAK/STAT signaling pathway - Huan Liu; Qianwei Li; Yuehong Chen; Min Dong; Hongjiang Liu; Jiaqian Zhang; Leiyi Yang; Geng Yin; Qibing Xie (Arthritis Research & Therapy)
Abstract Background Rheumatoid arthritis (RA) is a systemic disease that primarily manifests as chronic synovitis of the symmetric small joints. Despite the availability of various targeted drugs for RA, these treatments are limited by adverse reactions, warranting new treatment approaches. Suberosin (SBR), isolated from Plumbago zeylanica—a medicinal plant traditionally used to treat RA in Asia—possesses notable biological activities. This study aimed to investigate the effects and potential underlying pathways of SBR on RA. Methods Tumor necrosis factor-alpha (TNF-α) induced inflammation in RA-derived fibroblast-like synoviocytes (RA-FLS), and the expression of proinflammatory mediators was assessed using q-RT PCR and ELISA after treatment with various SBR concentrations. Bone marrow-derived macrophages (BMDMs) were induced to differentiate into M1 and M2 macrophages, followed by treatment with various SBR concentrations and macrophage polarization assessment. Low-dose (0.5 mg/kg/d) and high-dose (2 mg/kg/d) SBR regimens were administered to a collagen-induced arthritis (CIA) mouse model for 21 days, and the anti-arthritic effects of SBR were evaluated. Network pharmacology and molecular docking analyses were used to predict the anti-arthritic targets of SBR. The effect of SBR on the Janus kinase/signal transducer and activator of transcription (JAK/STAT) pathway was evaluated. Results SBR suppressed macrophage polarization toward the M1 phenotype while enhancing their polarization toward the M2 phenotype. SBR reduced the levels of proinflammatory mediators in TNF-α-induced RA-FLS. Mechanistically, SBR inhibited the phosphorylation of the JAK1/STAT3 signaling pathway in RA-FLS and M1 macrophages and promoted the phosphorylation of the JAK1/STAT6 pathway in M2 macrophages, enhancing M2 polarization. In vivo, prophylactic treatment of low-dose SBR reduced M1 macrophage infiltration into synovial tissue, increased the proportion of M2 macrophages, and decreased the expression of inflammatory mediators in the serum and synovial tissue, alleviating synovial inflammation. SBR significantly alleviated arthritis in CIA mice through macrophage repolarization and inhibition of inflammation. Conclusion SBR significantly reduced clinical symptoms, joint pathological damage, and expression inflammatory cytokine expression in CIA mice. SBR exhibited anti-arthritic effects via the JAK1/STAT3 and JAK1/STAT6 signaling pathways, inhibiting synovial tissue inflammation and M1 macrophage polarization while promoting M2 macrophage polarization. Therefore, SBR may be an effective candidate for RA treatment.